Role of a vacuolar iron transporter OsVIT2 in the distribution of iron to rice grains - Che, Jing; Yamaji, Naoki; Ma, Jian Feng (The New phytologist, 2021)
• Iron (Fe) from rice grains is an important source of dietary intake; however, the molecular mechanisms responsible for loading of Fe to the grains are poorly understood. • We functionally characterized a vacuolar iron transporter gene, OsVIT2 in terms of expression pattern, cellular localization, and mutant phenotypes. • OsVIT2 was expressed in the parenchyma cell bridges of nodes, in the mestome sheath of leaf sheath and aleurone of the caryopsis. Mutation of OsVIT2 resulted in decreased Fe distribution to the leaf sheath, nodes, and aleurone, but increased Fe to the leaf blade and grains. Furthermore, Fe was heavily deposited in the parenchyma cell bridges, mestome sheath and aleurone in the wild-type rice, but this accumulation was decreased in the knockout lines. Conversely, heavier deposition of Fe was observed in the embryo and endosperm of the grains of knockout lines compared with the wild-type rice, resulting in increased Fe accumulation in the polished rice without yield penalty. • These results indicate that OsVIT2 is involved in the distribution of Fe to the grains through sequestering Fe into vacuoles in mestome sheath, nodes, and aleurone layer and that knockout of this gene provides a potential way for Fe biofortification without yield penalty.